2016
DOI: 10.1186/s40900-016-0038-7
|View full text |Cite
|
Sign up to set email alerts
|

Giving voice to older adults living with frailty and their family caregivers: engagement of older adults living with frailty in research, health care decision making, and in health policy

Abstract: Plain English summaryThe paper discusses engaging older adults living with frailty and their family caregivers. Frailty is a state that puts an individual at a higher risk for poor health outcomes and death. Understanding whether a person is frail is important because treatment and health care choices for someone living with frailty may be different from someone who is not (i.e., who is fit). In this review, we discuss strategies and hurdles for engaging older adults living with frailty across three settings: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(100 citation statements)
references
References 56 publications
(64 reference statements)
4
90
1
4
Order By: Relevance
“…In older physicians, a rational decision‐making style showed a stronger positive effect on patient involvement in protocols. This could be seen as contrary to studies reported previously that older physicians are more intuitive (heuristic) in decision making and more paternalistic when interacting with patients . Female physicians utilizing slow/DMR showed a stronger positive effect on patient involvement in decision‐making tools than male physicians utilizing this form of decision making.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In older physicians, a rational decision‐making style showed a stronger positive effect on patient involvement in protocols. This could be seen as contrary to studies reported previously that older physicians are more intuitive (heuristic) in decision making and more paternalistic when interacting with patients . Female physicians utilizing slow/DMR showed a stronger positive effect on patient involvement in decision‐making tools than male physicians utilizing this form of decision making.…”
Section: Discussioncontrasting
confidence: 99%
“…This could be seen as contrary to studies reported previously that older physicians are more intuitive (heuristic) in decision making and more paternalistic when interacting with patients. 64,65 Female physicians utilizing slow/DMR showed a stronger positive effect on patient involvement in decision-making tools than male physicians utilizing this form of decision making. This is consistent with several earlier studies showing that female physicians are more participatory in terms of empathy and information sharing.…”
Section: Multi-groupmentioning
confidence: 99%
“…Frailty is often misconstrued to be a part of the normal aging process; the worst is that old patients are treated on the basis of their medical conditions alone, rather than accounting for their frailty status [8]. By identifying adults living with frailty, health and social care providers can implement programs focused on early detection, prevention, and management of the frailty in order to reduce future institutionalization, improve health outcomes, and enhance the quality of life of old people [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Gregory, Mackintosh, Kumar, & Grech, ; José, Barros, Samitca, & Teixeira, ). However, informal caregivers are also important actors to stimulate mastery in frail, older adults (Holroyd‐Leduc et al, ). Informal caregivers play an essential role in arranging and managing the continuity of care (Willemse et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Gregory, Mackintosh, Kumar, & Grech, 2017;José, Barros, Samitca, & Teixeira, 2016). However, informal caregivers are also important actors to stimulate mastery in frail, older adults (Holroyd-Leduc et al, 2016).…”
Section: Introductionmentioning
confidence: 99%